2012
DOI: 10.1161/circinterventions.112.972596
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Glomerular Filtration Rate After Renal Revascularization Correlate With Microvascular Hemodynamics and Inflammation in Swine Renal Artery Stenosis

Abstract: Background Selection of patients with renal artery stenosis (RAS) likely to improve glomerular filtration rate (GFR) after percutaneous transluminal renal angioplasty (PTRA) is difficult. We examined basal hemodynamic and inflammatory factors linked to improved stenotic kidney (STK) function after PTRA in swine RAS. Methods and Results Fifteen pigs after 6 weeks of hemodynamically-significant RAS were studied before and 4 weeks after technically-successful PTRA+stenting. STK and contralateral kidney (CLK) he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 48 publications
1
55
0
Order By: Relevance
“…In line with these observations, we have recently shown in swine ARAS that systemic infusion of Bendavia during the PTRS procedure (from 30min before to 3.5 hours after PTRS), promoted renal mitochondrial biogenesis and attenuated microvascular remodeling, apoptosis, oxidative stress, tubular damage, and fibrosis evaluated four weeks after revascularization [20]. Furthermore, renal inflammation, one of the main determinants of disease progression and response to revascularization in ARAS [21], was restored to normal levels in Bendavia-treated pigs. Remarkably, stenotic-kidney blood flow and glomerular filtration rate were normalized in animals treated with Bendavia, suggesting a unique potential of this drug for limiting renal reperfusion injury in chronic experimental ARAS.…”
supporting
confidence: 58%
“…In line with these observations, we have recently shown in swine ARAS that systemic infusion of Bendavia during the PTRS procedure (from 30min before to 3.5 hours after PTRS), promoted renal mitochondrial biogenesis and attenuated microvascular remodeling, apoptosis, oxidative stress, tubular damage, and fibrosis evaluated four weeks after revascularization [20]. Furthermore, renal inflammation, one of the main determinants of disease progression and response to revascularization in ARAS [21], was restored to normal levels in Bendavia-treated pigs. Remarkably, stenotic-kidney blood flow and glomerular filtration rate were normalized in animals treated with Bendavia, suggesting a unique potential of this drug for limiting renal reperfusion injury in chronic experimental ARAS.…”
supporting
confidence: 58%
“…[2] In a previous study, we found that stenotic swine kidneys in ARAS have increased tissue levels of the pro-inflammatory chemokine monocyte chemo-attractant protein (MCP-1), which is associated with endothelial dysfunction and microvascular loss. [26] Elevated systemic levels of tumor necrosis factor (TNF)-α and MCP-1 in ARAS patients also persist after revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Mean arterial pressure (MAP) was subsequently measured by a PhysioTel® telemetry system (Data Sciences International, St. Paul, MN) implanted at baseline in the left femoral artery and averaged in the last 2–3 days before study completion. [2,79] …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations